Pengenalan Peserta Didik dan Suasana Sekolah di SMA Negeri 1 Kuok - Mimis Saputra; Bunga Ervinasari; Astuti (PT PUSTAKA CENDEKIA GROUP, 2025)
This article aims to review information about Student Introduction and School Atmosphere at SMA Negeri 1 Kuok. The method used is an exploratory method. This research was conducted at SMA Negeri 1 Kuok. The subject of the research was one of the educators of the Mathematics study program at SMA Negeri 1 Kuok who teaches in class XII along with students of class XII at SMA Negeri 1 Kuok. The results of the study showed that the researcher gained new experiences and provided the researcher with extensive knowledge for the future in the teaching and learning process as a prospective student. The researcher can also find out the situation and conditions related to the school concerned. The implications of personality at SMAN 1 Kuok are very good, both for educators and students. Educators have mature, wise, authoritative and noble personalities who are role models for students. The implications of professional competence of educators and pedagogy in improving student learning outcomes at SMAN 1 Kuok have been implemented, but during the Covid19 pandemic, the implementation process was considered less than optimal. The less than optimal professional competence of educators has an impact on improving student learning outcomes. Pedagogical competence at SMAN 1 Kuok has been implemented and educators are able to manage student learning. The implications of social competence at SMAN 1 Kuok have been implemented, educators interact effectively and efficiently with students, fellow educators, education personnel, guardians of students and the community.